2020
DOI: 10.1080/00365521.2020.1739325
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic colitis and its associations with complications observed in classic inflammatory bowel disease: a systematic review

Abstract: Objectives: Crohn's disease and ulcerative colitis are associated with an increased risk to develop anemia, cutaneous diseases, liver diseases, malignancy, osteoporosis, rheumatic diseases, thromboembolism and uveitis. The association between these diseases and microscopic colitis (MC) is not known. The aim of the present systematic review was to examine associations between MC and diseases observed in association with Crohn's disease and ulcerative colitis. Material and methods: According to the review protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
4
0
3
Order By: Relevance
“…Los criterios actuales para el diagnóstico de estas dos entidades son los descritos en la clasificación de Roma IV, y se diferencian entre sí por el dolor abdominal que generalmente está ausente en la DF demostrado en otros estudios (12) . También se ha relacionado con el antígeno leucocitario humano DQ2, el cual se asocia con otras enfermedades autoinmunes y con alteraciones del microbioma fecal (disminución de la bacteria Akkermansia muciniphila) (10) .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Los criterios actuales para el diagnóstico de estas dos entidades son los descritos en la clasificación de Roma IV, y se diferencian entre sí por el dolor abdominal que generalmente está ausente en la DF demostrado en otros estudios (12) . También se ha relacionado con el antígeno leucocitario humano DQ2, el cual se asocia con otras enfermedades autoinmunes y con alteraciones del microbioma fecal (disminución de la bacteria Akkermansia muciniphila) (10) .…”
Section: Discussionunclassified
“…Muchos autores incluyen actualmente a la CM dentro del grupo de la EII, al lado de patologías tan importantes como la EC o la colitis ulcerativa (CU), aunque presenta características muy disímiles en cuanto a la edad, síntomas, evolución de la enfermedad y tratamiento. La EC y la CU a menudo se consideran enfermedades sistémicas, que además de afectar la región colorrectal se asocian frecuentemente con otras enfermedades y con complicaciones de tipo neoplásico, las cuales no se han podido demostrar en relación con la CM (10) .…”
Section: Diagnósticounclassified
“…MC is a clinicopathologic disorder, histologically subdivided into LC with increased intraepithelial lymphocytes (>20/100 colonic surface epithelial cells) and CC with atypically thickened subepithelial collagen band >10 μm [4]. MC is postulated to develop via an immunological response to various mucosal insults in predisposed patients [3].…”
Section: Discussionmentioning
confidence: 99%
“…IBD has known complications such as malignancy and immune-mediated diseases such as ankylosing spondylitis and autoimmune thyroid disease. A systematic review showed an association between rheumatic diseases and MC [4,5], but no real conclusions can be made regarding MC and its association with classic IBD complications [4]. The complication rates and prognosis with MC-IBD overlap are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking and some drugs are associated with the disease, although the causal mechanism cannot be proved. Complications commonly associated with Crohn's disease or ulcerative colitis; for example, malignancy and liver diseases, are not associated with MC 7 . Thus, the pathophysiology in MC should differ from the pathophysiology in classic inflammatory bowel disease.…”
mentioning
confidence: 99%